Τα ζώα στον προσβλητικό λόγο των Βυζαντινών - ΗΛΙΟΠΟΥΛΟΣ Παναγιώτης (Byzantina Symmeikta, 2021)
Abusive speech aims at the reprehension and humiliation of the target/ receiver. A desired outcome is also to dissasociate the person of interest by portraying it as an ostracized outcast from the dominant social norms. For this purpose, abusive speech uses various commonplaces (τόποι). Byzantine authors utilize extensively both the Ancient Greek as well as the Christian tradition as sources for these commonplaces. In addition, they utilize the literary tradition and the common knowledge about animals in order to compose an attack against an adversary. Animals appear very frequently in Byzantine abusive speech, as it is indicated by numerous examples presented in this paper.